THEORY CONCEPT OF DOROTHEA ELIZABETH OREM'S NURSING MODEL DOROTHEA ELIZABETH OREM: SELF-CARE IN NURSING CARE FOR MR. S WITH NON-HEMORRHAGIC STROKE AT MAYAPADA HOSPITAL - Tasya, Chindyca Anna; Nursanti, Irna (JOURNAL EDUCATIONAL OF NURSING(JEN), 2025)
This study aims to implement nursing care in a non-hemorrhagic stroke case in an inpatient setting, using Dorothea Orem's nursing model theory. The focus of this case study is to provide comprehensive nursing care to Mr. S based on Orem's conceptual framework. The research method used is a case study with a nursing care approach based on Orem's theory. Data were collected through interviews, observations, physical examinations, and using an assessment format adapted to Orem's nursing theory.The initial assessment of Mr. S revealed a blood pressure of 180/100 mmHg, a pulse rate of 80 beats/min, SpO2 of 95% with 3 lpm of oxygen, and a respiratory rate of 26 breaths/min. From this data, two primary nursing problems were identified: the risk of decreased cerebral tissue perfusion and an ineffective breathing pattern. Nursing interventions aligned with the Indonesian Nursing Outcome Standards (SLKI). After three days of nursing care for Mr. S, it was concluded that both nursing interventions had partially resolved the problem. This study recommends that nurses consistently implement and improve the quality of nursing care using Dorothea Orem's self-care theory.